Metastasis Risk of Cutaneous Squamous Cell Carcinoma in Organ Transplant Recipients and Immunocompetent Patients - Roel E. Genders; Joris A.J. Osinga; Elise E. Tromp; Peter O'Rourke; Jan N. Bouwes Bavinck; Elsemieke I. Plasmeijer (Medical Journals Sweden, 2018)
Organ transplant recipients (OTRs) have a high incidence of cutaneous squamous cell carcinoma (cSCC), and immunosuppression has been reported to be an important risk factor for metastasis. The aim of this study was to identify the metastasis risk over a 10-year period for 593 patients with cSCC, of whom 134 were OTR and 459 were immunocompetent. Metastasis incidence rate was 1,046 (95% confidence interval (95% CI) 524-2,096) per 100,000 person years in OTR and 656 (95% CI; 388-1,107) in immunocompetent patients, yielding an incidence rate ratio of 1.6 (95% CI 0.67-3.81). In OTRs head/neck location, older age at transplantation and older age at diagnosis of first cSCC were associated with metastatic risk, and 7 out of 8 metastasized tumours were smaller than 2 cm. In immunocompetent patients tumour size and tumour depth were associated with metastasis. In conclusion, we were not able to demonstrate an increased incidence rate of metastasis in OTRs compared with immunocompetent patients. However, OTRs and immunocompetent patients differed with regard to risk factors for metastasis.